2005
DOI: 10.1051/kmae:2005018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial and Microsatellite Dna Analyses of Austropotamobius Pallipes Populations in South Tyrol (Italy) and Tyrol (Austria)

Abstract: Historical data show that the native white-clawed crayfish, Austropotamobius pallipes, was once widespread throughout South Tyrol (northern Italy), whereas recent studies identified only half a dozen remaining populations. In order to implement conservation strategies based on knowledge of genetic diversity, each of the six remaining populations in South Tyrol and one population in Tyrol (Austria) were investigated by (i) sequencing segments of two mitochondrial DNA genes, 16S rRNA and cytochrome c oxidase sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…At each of the three polymorphic microsatellite loci employed in the present work only two different alleles were found. By comparison, a previous study investigating populations of A. pallipes in South Tyrol (Italy) found a total number of ten and nine different alleles at loci Ap3 and Ap6 (BARIC et al, 2005a). Similarly, overall heterozygosity was found to be lower in Carinthian (H O = 0.35) than in South Tyrolean populations (H O = 0.53), while it was comparable to that observed in a single brook in France (H O = 0.38; GOUIN et al, 2002).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…At each of the three polymorphic microsatellite loci employed in the present work only two different alleles were found. By comparison, a previous study investigating populations of A. pallipes in South Tyrol (Italy) found a total number of ten and nine different alleles at loci Ap3 and Ap6 (BARIC et al, 2005a). Similarly, overall heterozygosity was found to be lower in Carinthian (H O = 0.35) than in South Tyrolean populations (H O = 0.53), while it was comparable to that observed in a single brook in France (H O = 0.38; GOUIN et al, 2002).…”
Section: Discussionmentioning
confidence: 64%
“…However, the study was performed in a single brook and distances among study sites were much smaller than that in the present work. Indeed, in South Tyrol considerable population differentiation was found on a relatively small geographical scale together with moderate degrees of genetic variability within populations (BARIC et al, 2005a). It is believed that this region was naturally colonised by the white-clawed crayfish after the last glaciation about 15,000-10,000 years ago.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This view was later supported through genetic evidence by Baric et al (2005), who concluded that an Italian origin of the Lake Plansee population seems very likely. The 16S sequences from our German specimens completely matched those from northern Italy as well as from Lake Plansee in Austria.…”
Section: Discussionmentioning
confidence: 91%
“…Füreder and Hanel, 2000) Habitat assessments at reach, river and catchment scales (e.g. Füreder et al, 2002Füreder et al, , 2003 Extension of existing crayfish habitats Morphological and genotypical characterisation of populations studied (Sint et al, , 2007Füreder et al, 2009b) Morphological and genotypical characterisation of populations studied (Baric et al, 2005a(Baric et al, , 2005bFüreder et al, 2009b) Table II shows examples of recent action for crayfish conservation in two river catchments in northern England. In both of those catchments there is progressive invasion by non-native crayfish underway and the emphasis in action for conservation is to find and protect safe, isolated ark sites for A. pallipes and minimize the risk of further human-assisted spread of P. leniusculus.…”
Section: Gain Knowledge About Threatsmentioning
confidence: 99%